1985
DOI: 10.1111/j.1471-4159.1985.tb05427.x
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Transport of Glycoconjugates in the Rat Visual System

Abstract: Long-Evans rats at 45 days of age were injected intraocularly with 25 mu Ci of [3H]glucosamine. Incorporation of radioactivity into retinal gangliosides, glycoproteins, and glycosaminoglycans (GAGs) was determined at various times after injection. Portions of all three classes of radioactive macromolecules were committed to rapid axonal transport in the retinal ganglion cells. With respect to gangliosides about 60% of those synthesized in the retina were retained in that structure, 30% were committed to transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…Columns were randomly checked during the course of the experiment and elution volumes for standards remained constant. Results of the calibration were consistent with those reported previously (Gammon et al, 1985). We assumed that much of the neutral glycolipid, reported by Aquino et al (19856) to be present in the axonally transported material of sensory neurons, would be removed in the solvent-aqueous partitions.…”
Section: Extraction and Separation Of Glycoconjugatessupporting
confidence: 89%
See 3 more Smart Citations
“…Columns were randomly checked during the course of the experiment and elution volumes for standards remained constant. Results of the calibration were consistent with those reported previously (Gammon et al, 1985). We assumed that much of the neutral glycolipid, reported by Aquino et al (19856) to be present in the axonally transported material of sensory neurons, would be removed in the solvent-aqueous partitions.…”
Section: Extraction and Separation Of Glycoconjugatessupporting
confidence: 89%
“…Both glycoproteins and gangliosides were isolated from each individual nerve segment. Gangliosides were extracted by a modification (Gammon et al, 1985) of the method of Ledeen and Yu (1978). Lyophilized DRG and nerve segments were sequentially extracted with 2 ml of CHC13/ CH30H/H20 (38:19:3) and 1 ml of CHCI3/CH3OH/H20 (19:38:3).…”
Section: Extraction and Separation Of Glycoconjugatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies on pronase digests of transported molecules have shown that both chondroitin sulfate (4 or 6) and heparan sulfate undergo axonal transport in the goldfish optic nerve (16,17) and the garfish olfactory nerve (18,19). Axonal transport of the same two glycosaminoglycans has been reported in a similar study on the rat optic nerve (20).…”
Section: Ripellino and E|ammentioning
confidence: 80%